An Introduction to the Qur’anic Hermeneutic of Irfan A. Khan - AZMAT, TANVEER (Islamic Studies, 2017)
This paper introduces Qur’anic hermeneutic of Irfan A. Khan (b. 1931), a significant scholar of the Qur’an and modern Western philosophy. Khan’s expertise in these two areas seems to result in a comprehensive theory and methodology of understanding the Qur’an. He is well versed in the modern hermeneutical theory, analytical philosophy, and event ontology on the one hand, and classical and modern methodologies of Qur’anic hermeneutics on the other. Khan in his writings and lectures did not indulge in philosophical or historical issues for the sake of keeping his focus on teaching the methodologies of understanding the Qur’an. He simply applied that knowledge in explaining the Qur’an. A significant contribution of this paper is to dig these hidden philosophical and Qur’anic arguments from Khan’s corpus and present them in a systematic and clear way to introduce his Qur’anic hermeneutic for further discourse.